2021
DOI: 10.1101/2021.12.09.471910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NITROGEN LIMITATION ADAPTATION functions as a negative regulator of Arabidopsis immunity

Abstract: Background: Phosphorus is an important macronutrient required for plant growth and development. It is absorbed through the roots in the form of inorganic phosphate (Pi). To cope with Pi limitation, plants have evolved an array of adaptive mechanisms to facilitate Pi acquisition and protect them from stress caused by Pi starvation. The NITROGEN LIMITATION ADAPTION (NLA) gene plays a key role in the regulation of phosphate starvation responses (PSR), its expression being regulated by the microRNA miR827. Stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Overexpression of AtCPK1 leads to increased resistance of plants upon necrotrophic attack, the molecular regulation for this is, however, so far unknown (Coca and San Segundo 2010 ). The suggested downregulation of AtNLA upon necrotrophic interaction (Val-Torregrosa et al 2021 -preprint) would lead to a potential reduction in AtORE1 degradation. Overall, this would increase AtORE1 activity and PCD as well as senescence (Oh et al 1997 ; Kim et al 2009 ; Balazadeh et al 2010 ; Farage-Barhom et al 2011 ; Al-Daoud and Cameron 2011 ; Matallana-Ramirez et al 2013 ; Qiu et al 2015 ; Durian et al 2020 ).…”
Section: Regulation Of Amino Acid Transporters Through Additional Phy...mentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of AtCPK1 leads to increased resistance of plants upon necrotrophic attack, the molecular regulation for this is, however, so far unknown (Coca and San Segundo 2010 ). The suggested downregulation of AtNLA upon necrotrophic interaction (Val-Torregrosa et al 2021 -preprint) would lead to a potential reduction in AtORE1 degradation. Overall, this would increase AtORE1 activity and PCD as well as senescence (Oh et al 1997 ; Kim et al 2009 ; Balazadeh et al 2010 ; Farage-Barhom et al 2011 ; Al-Daoud and Cameron 2011 ; Matallana-Ramirez et al 2013 ; Qiu et al 2015 ; Durian et al 2020 ).…”
Section: Regulation Of Amino Acid Transporters Through Additional Phy...mentioning
confidence: 99%
“…Interestingly, also plants infected with necrotrophs displayed increased resistance, although no ET derived defense responses were found (Coca and San Segundo 2010 ). In a preprinted study, it was suggested that AtNLA displays a negative regulator in plant defense against necrotrophs (Val-Torregrosa et al 2021 -preprint). nla mutants displayed increased callose deposition as well as increased resistance.…”
Section: Regulation Of Amino Acid Transporters Through Additional Phy...mentioning
confidence: 99%
See 1 more Smart Citation